2017
DOI: 10.1002/2017ja024763
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Modification of the Force Field Approach to Describe the Modulation of Galactic Cosmic Rays Close to Earth in a Broad Range of Rigidities

Abstract: On their way through the heliosphere, galactic cosmic rays (GCRs) are modulated by various effects before they can be detected at Earth. This process can be described by the Parker equation, which calculates the phase space distribution of GCRs depending on the main modulation processes: convection, drifts, diffusion, and adiabatic energy changes. A first‐order approximation of this equation is the force field approach, reducing it to a one‐parameter dependency, the solar modulation potential ϕ. Utilizing this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 56 publications
0
40
1
Order By: Relevance
“…Since we have shown that the calculated dose rate is rather insensitive to the actual value of / (Fig. 5) and since the topic being discussed focuses on discussing measurement principles, rather than predicting future absorbed dose rates, we will use the / PP by Gieseler et al (2017)…”
Section: Generating a Time Series And Comparing With Datamentioning
confidence: 99%
“…Since we have shown that the calculated dose rate is rather insensitive to the actual value of / (Fig. 5) and since the topic being discussed focuses on discussing measurement principles, rather than predicting future absorbed dose rates, we will use the / PP by Gieseler et al (2017)…”
Section: Generating a Time Series And Comparing With Datamentioning
confidence: 99%
“…However, the approach, among others, neglects adiabatic cooling processes and can depend on additional parameters such as the magnetic field structure, particle drifts, stellar cycle, etc. (Gieseler et al 2017, and references therein). Thus, an application of the FFA to other stars requires knowledge of the astrospheric turbulence (represented by κ) as well as the stellar wind velocity.…”
Section: Introductionmentioning
confidence: 99%
“…We will validate our results against three of the published measurements performed on 16 April 1965, on 29 July 1967, and on 2 August 1969 (values given in their Table 4). Based on the LIS by Herbst et al () and the modified modulation parameter ϕ by Gieseler et al () the following corresponding ϕ values were used: ϕ 1965 = 380 MV, ϕ 1967 = 665 MV, and ϕ 1969 = 950 MV. For helium, the modulation parameter was one half of the proton ϕ .…”
Section: Validationmentioning
confidence: 99%
“…In order to validate against Earth measurements, AtRIS was used with atmospheres generated using the NRLMSISE-00 model (Picone et al, 2002), using all available gas species (N, N 2 , O, O 2 , Ar, He, and H). Primary spectra were obtained by following the modified force field approach outlined in Gieseler et al (2017) based on the LIS model by Burger et al (2000), Herbst et al (2017), Usoskin et al (2011), and references therein. For each validation case, we provide the modulation parameters that have been used.…”
Section: Validationmentioning
confidence: 99%